ANALYZING IDIOMATIC TRANSLATION IN TAYLOR SWIFT’S RED - Badri; Siti Juleha (Politeknik Negeri Jakarta, 2026)
This study analyzes the translation of idiomatic expressions in Taylor Swift's song lyrics on her album “Red” from English into Indonesian. Idiomatic expressions are often difficult to translate because their meaning cannot be understood literally based on the words they are composed of. This study aims to identify idiomatic expressions found in song lyrics, analyze the translation techniques used in the Indonesian translation, and describe how the translator maintains the equivalence of meaning and emotional nuance in the resulting translation. This study uses a qualitative descriptive method. Data were taken from several song lyrics on the album *Red* containing idiomatic expressions, then analyzed using Newmark's translation theory and Baker's concept of idioms. The results show that there are three main techniques used in translating idioms: literal translation, free translation, and cultural substitution. Literal translation and free translation techniques were each used 40% of the time, while cultural substitution was used 20%. Free translation is more dominant in idioms with strong emotional meaning, while literal translation is used for idioms with direct structural equivalents in Indonesian. This research also shows that preserving emotional meaning is more important than preserving the original linguistic form. Therefore, translating idioms into song lyrics requires an understanding of language, culture, and emotional nuances to effectively convey the song's message and aesthetic value.